Improving conservation effectiveness of nature reserve for golden snub‐nosed monkey, a niche‐based approach. Issue 18 (24th August 2018) - Yan, Zhaogui; Teng, Mingjun; He, Wei; Wang, Yuan; Yang, Jingyuan; Wang, Pengcheng
Abstract: Reserve selections are often opportunistic rather than strategic and coordinated, and consequently, many reserves are ineffective to achieve their intended goals of conservation. Here, we assessed the conservation effectiveness of a reserve for the golden snub‐nosed monkeys ( Rhinopithecus roxellana ) with a niche‐based approach. We assessed habitat usage of the monkeys in Shennongjia Nature Reserve (SNR) and attributes of 14 environmental variables that could potentially affect the monkeys' habitat use. Spatial distribution of potentially suitable habitat for the monkeys was then modeled with Maxent, a niche‐based model, and conservation effectiveness of SNR was assessed by comparing the current boundary of the reserve with the spatial distribution of the modeled potential habitat and the current habitat area of the monkeys. Only 59% of the habitat area and 61% of the predicted potential habitat area were under the protection of SNR. To improve conservation effectiveness of SNR, we proposed that the current SNR be enlarged by 270 km 2 . The enlarged reserve would encompass 100% of the existing habitat area plus 89% of the predicted potential habitat area. Using the niche‐based approach, we were able to integrate habitat usage data of the target species with that of remote sensing to identify areas potentially suitable as habitat for the species. This information can be used not only for improving conservation effectiveness of existing reserves but also for the effective planning and designing of new reserves. Abstract : We assess the effectiveness of nature reserve in achieving its intended goals of conservation by comparing the current boundary of the reserve with the spatial distribution of the modeled potential habitat and the current activity area of the focal species. Using new information on the target species (or habitats) in the context of changed social and economic conditions, our study demonstrates how the adequacy of an existing reserve can be reassessed and inadequacies addressed to improve its effectiveness of conservation. Of equal importance, our study has also shown how niche‐based models, such as Maxent, can be used to identify potential habitat for a target species and can facilitate nature reserve design and selection for conservation of that species.